(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Military terminology constitutes an important part of the lexical system of any language and reflects the military, historical, and cultural development of a nation. Military position titles represent a specific lexical-semantic layer within military terminology, serving not only nominative but also communicative and administrative functions. This article examines the lexical-semantic groups of military position titles in English and Uzbek languages. Through comparative linguistic analysis, similarities and differences in the classification, semantic structure, and functional usage of military position names are identified. The study demonstrates that despite structural differences between the two languages, military position titles share common semantic characteristics determined by the hierarchical organization of military institutions.